ANALISIS PENERAPAN INTERNATIONAL ACCOUNTING STANDARD (IAS) 41 PADA PT. SAMPOERNA AGRO, Tbk - Adita Adita; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
Biological assets are plant and animal live which have biological transformation. Biologicaltransformation consists of a process of growth, degeneration, production, and procreation thatcause qualitative and quantitative changes. Standards which arrange the biological asset is IAS 41.The analysis of this study was conducted using comparative qualitative method through a casestudy in one of the farm company which is listed in Indonesia Stock Exchange, PT. SAMPOERNAAGRO, Tbk. The data which is used is secondary data from annual report in 2011. The analysis ofthis data was processed using descriptive quantitative method in order to find the impact of theapplication of IAS 41 in that company. The results of this study showed there was no significantdifferent between the measurement, recognition, and disclosure of biological assets before andafter applied IAS 41. But when IAS 41 was applied there was no confession about the existence ofaccumulation depreciation, so that there is an increase of those biological assets. Themeasurement of biological assets used fair value so that it is more relevant than today. Thebiological assets are grouped based on the age of the plant to measure the fair value.